(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The article explores the political views and political activities of Mahmudhaja Behbudi , a major political and educational figure who lived and worked in Turkestan at the beginning of the 20th century, the father of the jadids of Central Asia. The study analyzes Behbudi’s views on the development of national identity, reform, education and culture, as well as his interaction with the jadidism movement and various political forces.